Long term Depot Medroxy Progesterone Asetate (DMPA) Injectable Increase Changes in Lipid Profiles of DMPA Injection Contraceptive Acceptors - Ririn Handayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
DMPA injectable contraceptives can cause changes in lipoprotein metabolism. Long term use of DMPA increases triglyceride levels, total cholesterol and LDL and decreases HDL levels. So, it can be concluded that DMPA can cause changes in lipid metabolism which can increase the risk of cardiovascular disease. Changes in fat metabolism occur due to the influence of the hormonal progesterone, which causes disruption of the balance of the lipid profile in the body. The purpose of this study was to determine the effect of using Depo Medroxy Progeserone Acetate injection on the lipid profile of three months injection family planning acceptors based on the duration of use.This research is an analytic observational study with a cross sectional approach, the population in this study were all DMPA family planning acceptors in the work area of ​​the Banjar Sengon Community Health Center, the sampling technique used was total sampling with a sample size of 30. Examination of the lipid profile was carried out by taking blood samples and then measuring them. lipid profile using the enzymatic colorimetric method (cholesterol oxidase method / CHOD PAP). The measurement results obtained were then analyzed using the Independent T test. The results of the T test analysis showed that the P value for cholesterol levels was 0.016 (P <0.05); The p value for triglyceride levels was 0.004 (P <0.05); The p value for HDL levels was 0.046 (P <0.05); The p value for LDL levels was 0.004 (P <0.05).From these data it can be concluded that there is a significant difference in the average levels of cholesterol, triglycerides, HDL, LDL between respondents with a duration of use <3 years and> 3 years. Respondents are expected to carry out routine lipid profile checks to detect early detection of possible abnormalities in lipid profiles that can lead to the risk of heart defects and stroke.